Phosphonic acid functionalization of nanostructured Ni–W coatings on steel - Orrillo, Patricio Andrés (2018)
The functionalization of nanocrystalline Ni–W coatings, formed by galvanostatic pulsed electrodeposition on steel, by thermal treatment of octadecylphosphonic acid self-assembled on the oxidized alloy surface is studied by Raman spectroscopy, contact angle measurements, X-ray photoelectron spectroscopy, AFM and electrochemical techniques. Results show that this procedure preserves the surface topography and the optimum mechanical properties of the alloy. More importantly, it turns the alloy surface highly hydrophobic and markedly improves its corrosion resistance, in particular to pitting corrosion in aggressive solutions containing chloride anions. The ability of the phosphonate layer to improve surface properties arises from the barrier properties introduced by the hydrocarbon chains and the strong bonds between the phosphonate head and the underlying surface oxides.